PEMBUATAN MEDIA PEMBELAJARAN MENGGUNAKAN CANVA PADA PELATIHAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KABUPATEN MUBA - Sri Sunarti (Balai Diklat Keagamaan Palembang, 2022)
The purpose of this study was to find out the extent of the competence of trainees in making learning media using canva in MUBA Regency. The research method used is a quantitative descriptive method where the researcher makes an image or descriptive about a situation objectively using numbers, starting from data collection, interpretation of the data and appearance and results. This research was conducted at Madrasah Aliyah Negeri 1 MUBA with a sample of 35 participants in learning media training based on information and communication technology. Data collection techniques through pretests and post-tests as well as participant results or products. The result of this study is that with the training of learning media based on information and communication technology, there is an increase in knowledge and skills related to making learning media using Canva. This proves that training in information and communication technology-based learning media with Canva is very beneficial for teachers.